Where the wild things are...stored? The management and return of seized wildlife - Saito, Anna (Frontiers Media S.A, 2025)
As more and more wildlife is seized across the globe due to the unlawful possession, handling and trading of protected wildlife species, the wildlife which needs to be managed by enforcement agencies keeps expanding. While seizure data alone is deemed insufficient to measure the illegal wildlife trade, given the complexity of the many drivers and pressures associated, the elevated numbers of wildlife seized provide nevertheless evidence of a global illicit trade that is in progress and seemingly prospering. Disentangling what happens to seized wildlife can be difficult. By using multiple methods including documentary analysis, seizure data analysis and key informant interviews, this study examines seizure management in four countries: Kenya and Uganda in East Africa and Germany and Czech Republic in Central Europe. Wildlife continues to be treated in many instances even after seizure on the basis of continued commodification, or enters a transient state of simultaneous commodification and decommodification, which influences seizure management framing and implementation. Dismissed as the unfortunate collateral of the illegal wildlife trade, live animals, dead animals and derivatives pass in the background. While seizure management processes are underdeveloped, patchy, neglected or burdened by resource constraints, responsible authorities, institutions and individuals struggle to find adequate solutions. By laying this much-needed groundwork for understanding seizure management in practice, opportunities to build on this work to investigate more substantive questions around conservation, environmental and restorative justice are created.